Melting Pot or Salad Bowl: Metro Manila's Cultural Heterogeneity - Soriano, Ronald N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Metro Manila is the bustling capital of the Philippines that has varied cultural influences. This study determined the perceptions of 200 respondents from selected government and private companies’ employees in the National Capital Region towards Metro Manila’s Salad Bowl of Homogeneity and Cultural Heterogeneity. Concurrent Triangulation was utilized to gather the perceptions of 200 government and private companies’ employees and corroborate findings within the study. Based on the results, people who keep in touch with their immediate kin and sometimes visit home to celebrate usual practices have the highest mean score of 3.25. On the other hand, people who were born in Metro Manila to parents who were from provinces thrive to learn about their native culture and family practices have the lowest mean score of 2.12, such that Metro Manila is a cultural melting pot due to its cultural heterogeneity. Metro Manila is a blend of the world’s culture, food, and languages, and diverse way of life.